Recognition of Indigenous Peoples' Jurisdiction over Water: Comparison of Law in Indonesia and New Zealand - Fatma Idris Rumalutur (Fakultas Hukum, Universitas Warmadewa, 2024)
This article argues that various water management issues in Indonesia today are caused by water governance that is still uniform between one region and another. In addition, water management law in Indonesia is still state-centric. On the other hand, the existence of customary law communities in Indonesia is still legally recognized by the state. By using the comparative law method, where I compare the laws in Indonesia and New Zealand, the findings of this research show that the granting of jurisdiction to indigenous peoples in the management of water resources in New Zealand shows the seriousness of the state to reform water management and truly strive for sustainable water management. The New Zealand government recognizes that water management using customary law can be a solution to water governance.